Minimally invasive repair of pectus excavatum (MIRPE) in adults: is it a proper choice? - Ezel Erşen; Ahmet Demirkaya; Burcu Kılıç; Hasan Volkan Kara; Osman Yakşi; Nurlan Alizade; Özkan Demirhan; Cem Sayılgan; Akif Turna; Kamil Kaynak (Videosurgery and Other Miniinvasive Techniques)
Introduction : The Nuss procedure is suitable for prepubertal and early pubertal patients but can also be used in adult patients. Aim : To determine whether the minimally invasive technique (MIRPE) can also be performed successfully in adults. Material and methods : Between July 2006 and January 2016, 836 patients (744 male, 92 female) underwent correction of pectus excavatum with the MIRPE technique at our institution. The mean age was 16.8 years (2–45 years). There were 236 adult patients (28.2%) (> 18 years) – 20 female, 216 male. The mean age among the adult patients was 23.2 years (18–45 years). The recorded data included length of hospital stay, postoperative complications, number of bars used, duration of the surgical procedure and signs of pneumothorax on the postoperative chest X-ray. Results: MIRPE was performed in 236 adult patients. The average operative time was 44.4 min (25–90 min). The median postoperative stay was 4.92 ±2.81 days (3–21 days) in adults and 4.64 ±1.58 (2–13) in younger patients. The difference was not statistically significant (p = 0.637). Two or more bars were used in 36 (15.8%) adult patients and in 44 (7.5%) younger patients. The difference was not statistically significant either (p = 0.068). Regarding the overall complications, complication rates among the adult patients and younger patients were 26.2% and 11.8% respectively. The difference was statistically significant (p = 0.007). Conclusions : MIRPE is a feasible procedure that produces good long-term results in the treatment of pectus excavatum in adults.